2014
DOI: 10.1039/c4ra01595a
|View full text |Cite
|
Sign up to set email alerts
|

Novel polyoxadiazoles with non-coplanar ortho-linked structures as highly CO2 permselective membranes

Abstract: A novel class of polyoxadiazole membranes containing non-coplanar 1,1′-thiobis(2-naphthoxy) groups was synthesized using versatile route and tested for CO2 separation. Upon oxidation, the sulfone-containing membranes exhibited higher permeability and lower selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Among all designing strategies, structural modification of monomers is the most powerful and versatile techniques for synthesis of processable high performance polymers. In this regard, introduction of flexible bonds, kinked structures, alicyclics, and bulky groups were frequently considered . Another structural modification approach to enhance the processability of rigid‐rod polymers is by modifying the substitution pattern of aromatic units in the main chain .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among all designing strategies, structural modification of monomers is the most powerful and versatile techniques for synthesis of processable high performance polymers. In this regard, introduction of flexible bonds, kinked structures, alicyclics, and bulky groups were frequently considered . Another structural modification approach to enhance the processability of rigid‐rod polymers is by modifying the substitution pattern of aromatic units in the main chain .…”
Section: Introductionmentioning
confidence: 99%
“…Hence, inclusion of n,n ′‐disubstituted biphenylene ( n = 1–3) and 1,2‐linked units derived from ortho ‐catenated aromatic rings are mainly used. Since 2006, our group has started a systematic project to develop processable polymers using various ortho ‐linked sulfide‐, sulfoxide‐, and sulfone‐containing monomers . It was found that the phenyl rings are forced by the ortho ‐linked pattern into a noncoplanar conformation which improves processability through reducing intermolecular forces between the polymer chains and lowering crystallization tendency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation